Journal of Preventive Medicine and Hygiene 2021
DOI: 10.15167/2421-4248/jpmh2021.62.3.1785
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences & mental health – the urgent need for public health intervention in India

Abstract: Summary Global evidence has demonstrated that Adverse Childhood Experiences (ACEs) up to age 18 significantly increases the risk of mental and physical health for an adult. The research linking ACE with health and well-being has confirmed a dose-response relationship between the number of ACEs experienced and the extent of the impact on wellbeing. The source of ACE is the family, community, and the immediate environment, and it causes long-term risk for mental health with the potential to carry it o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…The findings of the present study underscore the need to consider ACE prevention strategies and programs for alleviating the burden of mental health disorders in India. National-level mental health programs should include ACE screening and prevention as a key component (Trivedi et al, 2021). Besides national policies, healthcare units and educational institutes can play important roles in fostering ACE prevention and mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study underscore the need to consider ACE prevention strategies and programs for alleviating the burden of mental health disorders in India. National-level mental health programs should include ACE screening and prevention as a key component (Trivedi et al, 2021). Besides national policies, healthcare units and educational institutes can play important roles in fostering ACE prevention and mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to food insecurity, adverse childhood experiences (ACEs) are a public health crisis that is harmful and responsible for insurmountable traumatic intrafamilial events. ACEs refer to instances of physical, emotional, sexual, or general maltreatment occurring during the rst 17 years of life (Boullier & Blair, 2018;Felitti et al, 1998;Trivedi et al, 2021;. ACEs encompass events such as parental divorce, witnessing intimate partner violence, parental mental illness, economic hardship, parental or guardian imprisonment, maltreatment, abuse, neglect, and household dysfunction, which are often categorized into physical, sexual, and emotional violence (Brown et al, 2023;Hughes et al, 2017;Negriff, 2021;Chipalo & Jeong, 2024).…”
Section: Adverse Childhood Experiences and Food Insecuritymentioning
confidence: 99%
“…This study found that ACEs were present across all demographic groups and had cumulative negative effects on an individual’s health. Since then, ACEs have been repeatedly linked to negative health outcomes in children and adults, including an increased risk for cardiovascular diseases [ 2 , 3 , 4 , 5 ]. Childhood is arguably the most vulnerable period of human life [ 6 ].…”
Section: Introductionmentioning
confidence: 99%